Attitudes and perceptions about ageism among nursing students: a scoping review - Jack Roberto Silva Fhon; Natalia Alves; Alexandre Pereira dos Santos Neto; Alice Regina Felipe Silva Djinan; Anaclara Viggiano Laurenti; Eveline Fontes Costa Lima (Universidade de São Paulo, 2024)
Objective: to map scientific knowledge on nursing students' attitudes and perceptions regarding ageism. Method: scoping review according to the recommendations of the Joanna Briggs Institute. The study question was: What are scientific evidence available on the attitudes and perceptions of nursing students regarding ageism? The search was conducted in 12 databases using the Rayyan application and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. The studies were selected by two reviewers using a data extraction tool. Results: of the 4,595 files, 46 that were published between 1984 and 2022 were selected, and the quantitative method was the most used. The most commonly used instrument was the Kogan's Attitudes Toward Old People Scale. Positive, negative, mixed, neutral, and inconclusive attitudes and perceptions were identified. Conclusion: attitudes and perceptions about ageism are diverse and not conclusive. Future intervention studies are recommended to detect changes in the behavior of nursing students in the face of ageism.